Hyperprolactinaemia – a problem in patients from the reproductive period to the menopause - Pałubska, Sylwia; Adamiak-Godlewska, Aneta; Winkler, Izabela; Romanek-Piva, Katarzyna; Rechberger, Tomasz; Gogacz, Marek (Menopause Review/Przegląd Menopauzalny, 2017)
Hyperprolactinaemia especially affects women in reproductive age (90/100,000) but also often is diagnosed in menopause age and leads to disturbances in functioning of LH-RH neurons and, as a consequence, to a decrease of FSH and LH, which causes inhibition of oestradiol production. Prolactin is a peptide hormone, phylogenetically one of the oldest, stimulating cells of various organs, which is produced and secreted mainly by lactotrophic acidophilic cells of the anterior lobe of the pituitary. It influences the increase in the mass of the mammary glands, and stimulation and maintenance of lactation after delivery. There are a number of factors apart of pregnancy, delivery, and lactation than can influence secretion of the hormone in other physiological and pathological circumstances, like high-protein diet, stress, REM sleep, or neoplastic tumours, inflammatory diseases, chronic systematic diseases, thyroid hormonal changes, and drug intake. The purpose of this review is to summarise the current knowledge regarding the proper diagnosis and possible influence of hyperprolactinaemia on fertility and menopause symptoms and current treatment methods